Assessment of Welfare in Transhumance Yak Hybrids (Chauris) in the Lower Himalayan Region of Nepal - Sapkota S; Laven R; Barsila SR; Kells N; Mueller KR; Dhurba DC (MDPI (Basel, Switzerland), 2024)
In order to develop a yak/chauri-specific welfare assessment protocol, we sent a set of 31 potential welfare measures to 120 Nepalese experts and asked them to identify the measures that they thought would be useful and propose additional useful measures. Eighty-three experts responded, with 13 measures being identified by >50% of respondents as likely to be useful. These thirteen measures plus one new measure (hematology) were included in an assessment protocol that was tested in the second phase of this study in five chauri herds in two districts in northern Nepal. Animal-based evaluations along with sampling for mastitis, intestinal parasites, and hematology were undertaken during or just after morning milking. Resource- and record-based measures were assessed through structured interviews, with verifications on-site where possible. No chauris exhibited poor body conditions, skin injuries, significant locomotion issues, or significant subclinical mastitis. Fecal testing suggested a high prevalence of intestinal parasites at the herd level, while blood testing suggested no evidence of hematological abnormalities. However, for both results, we need more data to use these effectively as measures of welfare. The resource-based assessment revealed significant challenges across all resources, and veterinary services were reported as being inadequate. A high estimated annual mortality rate (10–21%) needs further investigation. This protocol provided a useful start towards developing a welfare assessment protocol for yak/chauri and identified issues that need addressing to optimize chauri welfare.
Keywords: chauri; welfare assessment protocol; welfare measures; yak